2004
DOI: 10.1097/01.ta.0000068995.63201.0b
|View full text |Cite
|
Sign up to set email alerts
|

The Value of the Ankle???Brachial Index for Diagnosing Arterial Injury After Knee Dislocation: A Prospective Study

Abstract: The ABI is a rapid, reliable, noninvasive tool for diagnosing vascular injury associated with knee dislocation. Routine arteriography for all patients with knee dislocation is not supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
121
0
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(132 citation statements)
references
References 13 publications
0
121
0
10
Order By: Relevance
“…However, they also state that all knee dislocation patients presenting to their institution since 2005 are now assessed with Ankle Brachial Indices (ABI), with an ABI of less than 0.8 necessitating further work up with angiogram. Mills et al [3] showed that an ABI \ 0.9 is highly predictive of major vascular injury, so we caution the reader that 0.9 should be used as a cut off, not 0.8. When indicated, we currently use CT-angiogram (CTA) as opposed to conventional angiogram as CTA has been shown to be highly sensitive and specific; it uses the anticubital fossa as opposed to the groin for injection site, and uses one-fourth the radiation [4].…”
mentioning
confidence: 99%
“…However, they also state that all knee dislocation patients presenting to their institution since 2005 are now assessed with Ankle Brachial Indices (ABI), with an ABI of less than 0.8 necessitating further work up with angiogram. Mills et al [3] showed that an ABI \ 0.9 is highly predictive of major vascular injury, so we caution the reader that 0.9 should be used as a cut off, not 0.8. When indicated, we currently use CT-angiogram (CTA) as opposed to conventional angiogram as CTA has been shown to be highly sensitive and specific; it uses the anticubital fossa as opposed to the groin for injection site, and uses one-fourth the radiation [4].…”
mentioning
confidence: 99%
“…As they explained, many of the patients included in their meta-analysis had injuries that occurred more than 30 years ago, and when interpreted in the context of the changing demographics of modern society, it would seem valuable to continue reporting the diagnostic utility of various physical examination maneuvers. Although some authors [18,21,24] agree that knee dislocations are best diagnosed and managed through a systematic approach, the specifics of such have been heavily debated [12,13,24]. Levy et al [10] reported a shortage of high-quality evidence from which to base diagnosis and treatment decisions, specifically those related to vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Levy et al [10] reported a shortage of high-quality evidence from which to base diagnosis and treatment decisions, specifically those related to vascular injury. Routine arteriography has been advocated by some [1,13], although there has been a gradual shift in opinion toward more selective use of angiography [6,9,16]. We therefore performed a review of a large trauma database and asked the following questions: (1) What patient factors are predictors of vascular injury after knee dislocation?…”
Section: Discussionmentioning
confidence: 99%
“…An anklebrachial index (ABI) should be performed if any concern of arterial injury arises following physical examination. Mills et al reported a 100 % sensitivity and specificity with ABIs <0.9 for patients with a clinically significant arterial injury [27]. If the vascular physical examination is normal the patient should be admitted and observed for at least 48 hours to make certain a late vascular occlusion does not occur [25].…”
Section: Diagnosismentioning
confidence: 99%
“…Isolated edema medially is often indicative of an isolated MCL injury. An effusion of the knee often results from intra-articular pathology, such as injury to the cruciate ligaments, or meniscus [10,13] [25][26][27][28]. Injury to the popliteal artery can be limb threatening and should be addressed promptly.…”
Section: Diagnosismentioning
confidence: 99%